The Analysis of Liquidity and Its Effect on Profitability, Sales and Working Capital Policy in Manufacturing Companies Listed on Indonesia Stock Exchange - Muzakir Achmady; Isni Andriana; Kemas Muhammad Husni Thamrin (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2020)
This study aims to analyze the liquidity through cash conversion cycle management and to examine the effect of liquidity on profitability, sales and working capital policy in manufacturing companies listed on Indonesia Stock Exchange in the period 2014-2018. Profitability is proxied by return on asset, sales (Total Sales) and working capital policy (Short-term debt to assets and current assets to total assets). The population of the study is manufacturing companies listed on Indonesia Stock Exchange. Purposive sampling method used as the sampling method. There are 21 manufacturing companies as the samples of the study. The type of data used in this study is quantitative and data sources of this study is secondary data. Descriptive statistic and simple linear regression analysis used as the research methodology. The result of descriptive analysis shows CCC benchmark of manufacturing companies is 95.0590 days with the highest value at 408.98 days and the lowest at -19.62 days. It is found that CCC has negative and significant effect on return on asset and total sales as well it has positive effect and significant on short-term debt to assets nevertheless CCC has positive but insignificant effect on current assets to total assets.